Perancangan dan Implementasi Sistem Informasi Peminjaman Buku Berbasis Web pada Perpustakaan Pribadi Menggunakan Framework Laravel - Tsania Aulia; Najla Nafila; Fero Triando; Fikri Hilabi (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to design and implement a web-based book borrowing information system for a private library using the Laravel framework. The research adopts an applied research approach within a software engineering paradigm, employing the Waterfall model to ensure systematic development, clear documentation, and procedural replicability. The study was conducted at Zahra’sBook, a small-scale private library characterized by limited resources and manual transaction management. Data were collected through structured observation, semi-structured interviews, and analysis of system artifacts, supported by relevant scientific literature. System development followed sequential stages, including requirements analysis, system design, implementation, and functional testing using black-box testing techniques. The results demonstrate that the developed system effectively supports core library services, including catalog management, borrowing and returning transactions, penalty calculation, and reporting. The implementation improves operational efficiency, data accuracy, and service transparency for both administrators and users.